DISTANCE EDUCATION AS A TOOL FOR DEVELOPING INTERCULTURAL COMPETENCE - Tiahur , Liubomyra (Distance Education in Ukraine: Innovative, Normative-Legal, Pedagogical Aspects, 2025)
The article explores the potential of distance education as an effective means of developing intercultural competence in a globalized society. It highlights the challenges inherent in intercultural interaction within online environments, particularly emotional distance, limited reflection, and the lack of practical tools. The relevance of implementing the Agile approach is substantiated as an adaptive educational strategy that combines technological efficiency with psychological and pedagogical mechanisms for developing the cognitive, emotional, behavioral, and reflective components of intercultural competence. A set of innovative tools is proposed (e.g., Mood Pulse, Story Points, Hero Story) that promote active student engagement, responsibility, and cultural sensitivity. The article provides theoretical generalizations, empirical guidelines, and recommendations for further implementation of Agile-based models in distance education.